Decision Enhancement Services - Keen, Peter G.W. (IOS Press, 2013)
Decision Enhancement (DE) is a field of practice aimed at extending lessons, principles and tools built up over a thirty year period, largely under the term ‘Decision Support’. Enhancement goes beyond support which has mostly focused on helping managers make use of interactive computer models and methods. DE substantially adds to the opportunities, especially in the use of the Internet as both an information resource and communications base for collaboration between groups but it also goes well beyond it in two important regards: a focus on enhancement of the processes that influence the quality of decisions that really matter in an organization; the ones that are most consequential, complex, and uncertain, and a shift from the design of computer- and telecommunications-based tools to a far more comprehensive ‘studio’ approach to the integration of change management, collaborative development and use, and a new generation of visual technology. DE is a lens that focuses on stakeholders in decision arenas and their decisions that matter. It continues with its invitation to bring stakeholders, domain experts and suite designers into its studios. The invitation extends to experts in domains relevant to making DE studios effective, as well as to the suite designers and providers of technology capabilities needed to provide the tools within the studio. DE provides services to guide a journey where executives, their advisors, change management specialists, experts in multi-disciplinary fields and technology developers can come together to make a substantive new impact on effective decision making in any organization. This book will add to the old - the proven lessons and expertise of these fields - and to their innovation. It is in this sense that it is an invitation and written to encourage reflection and discussion within and across them